Analisis Dampak Judi Online dan Strategi Intervensi Bimbingan dan Konseling: Sebuah Kajian Literatur - Suhur, M Khautalfata; Anas, Moh; Rizkyawan, Bimo Bagas; M, Muslikah; Mahfud, Ashari (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Online gambling has become an increasingly widespread phenomenon in society, especially among adolescents and young adults. Easy access through digital devices and lack of supervision and education have made online gambling grow rapidly and have a negative impact on various aspects of an individual's life, such as financial, psychological, social, and academic. Therefore, an effective guidance and counseling intervention strategy is needed to deal with online gambling addiction and help individuals in the recovery process. This study is a literature review conducted by searching for articles on Google Scholar with keywords related to online gambling and counseling intervention. Articles that meet the inclusion and exclusion criteria are then analyzed to identify the impact of online gambling and intervention strategies that can be applied by counselors. The literature review shows that online gambling has various negative impacts on individuals, namely: (1) financial disruption due to debt and loss of assets, (2) psychological disorders such as stress, anxiety, and depression, (3) social conflict that causes isolation and disunity in the family, and (4) decreased academic achievement due to lack of focus and motivation to learn. Some effective intervention strategies in dealing with online gambling addiction include cognitive behavioral therapy (CBT), religion-based therapy, individual counseling, group counseling, and community-based rehabilitation. Online gambling has a significant negative impact on various aspects of an individual's life. Therefore, appropriate guidance and counseling interventions are needed to help individuals overcome addiction and restore their quality of life.